Inter-Cultural Education in Latin America: An Analysis of Field Research in the Region [Educación Intercultural en Latinoamérica: Análisis de Las Investigaciones de Campo en la Región] - Villalta-Paucar, M (Pontificia Universidad Catolica de Valparaiso, 2016)
Inter-cultural education is a task and challenge for XXI century formal education. This article first deconstructs the concept of culture in order to show the intentiona-transformative character of the educational act and, on another key, reveals the notion of difference in the distinctions we make within our own peer group as opposed to those involving others. The goal of the article is to analyze the conclusions advanced by a set of field research endeavours about inter-cultural education on formal Latin American education. We used contents analysis in our methodological approach, covering thirty field research articles in Latin America, as published in scientific magazines between 2000 and 2013, using the EBSCO database. Results were organized along two dimensions: (a) cultural identity: The organization of internal differences versus others and (b) ethical-political: The social project of the educational endeavour. Finally, we deliver a systematic approach that contributes to understand and propose the underlying logic about the role of the difference and the educational endeavour in Latin American Inter-cultural Education. The studies converge in delimiting cultural differences that may serve as a beacon to inter-cultural educational endeavours.